Detection of Phytophthora cinnamomi on declining Araucaria araucana forests. Issue 5 (22nd August 2022) - Sanfuentes, Eugenio; González, Mariela; Castillo, Miguel; Rubilar, Rafael; Besoain, Ximena; Sanhueza, Claudia; Smith, Milena
Abstract: Since 2016, crown death and mortality of Araucaria araucana trees have been observed at different localities of the Nahuelbuta Coastal Range, Chile. The objective of this study was to determine the presence of Phytophthora spp. in the rhizosphere of A. araucana trees that may explain its decline. Samples of soil rhizosphere were collected from trees with crown death as well as from asymptomatic trees at two visually contrasting severity areas. Phytophthora detection from soil samples was carried out using leaf bait technique, and isolates were identified by morphology and molecular methods. Recovered Phytophthora isolates were used in pathogenicity tests with A. araucana plants. From rhizosphere soil samples of 30 A. araucana trees, 56 isolates of Phytophthora cinnamomi were obtained. Isolations were more frequent in the rhizosphere of trees with severe crown symptoms and originated exclusively from the selected area showing severe crown symptoms. Plant stem inoculation with P. cinnamomi isolates caused 100% mortality; however, through root infestation, mortality was variable depending on the specific isolate. These results are the first report of the pathogenicity of P.cinnamomi A2 in natural forests of A. araucana in Chile.